Exploring Edmodo: assisted writing formative assessment in English language classroom - Mita Meryani Zuwitasari; Muhamad Reza Pahlevi; Mobit Mobit (Politeknik Negeri Bali, 2021)
This study aims to explore the use of Edmodo in formative assessment and students' perceptions on the use of Edmodo writing. This study uses a basic interpretive design. An English teacher and seven students participated in this research. It used observations, interviews, and documentation to collect data to answer these two research questions. The findings showed that the Edmodo-assisted writing formative assessment builds teacher technological pedagogy, and content knowledge. The students’ responses are viewed from cognitive aspect. Furthermore, the students can improve and explore the ability to writing skills. From the emotional perspective, the students feel more enjoyable and enthusiastic when doing a formative test. Whereas in the affective perspective, the students seemed more interested in assessment manually by the teacher through individual correction analysis.